Complete genome sequence and analysis of Alcaligenes faecalis strain Mc250, a new potential plant bioinoculant - Felestrino, Érica Barbosa; Sanchez, Angélica Bianchini; Caneschi, Washington Luiz; de Carvalho Lemes, Camila Gracyelle; de Almeida Barbosa Assis, Renata; Cordeiro, Isabella Ferreira; Fonseca, Natasha Peixoto; Villa, Morghana Marina; Vieira, Izadora Tabuso; Kamino, Luciana Hiromi Yoshino; Do Carmo, Flávio Fonseca; Da Silva, Aline Maria; et al. (Public Library of Science (PLoS), 2020)
Here we present and analyze the complete genome of Alcaligenes faecalis strain Mc250 (Mc250), a bacterium isolated from the roots of Mimosa calodendron, an endemic plant growing in ferruginous rupestrian grasslands in Minas Gerais State, Brazil. The genome has 4,159,911 bp and 3,719 predicted protein-coding genes, in a single chromosome. Comparison of the Mc250 genome with 36 other Alcaligenes faecalis genomes revealed that there is considerable gene content variation among these strains, with the core genome representing only 39% of the protein-coding gene repertoire of Mc250. Mc250 encodes a complete denitrification pathway, a network of pathways associated with phenolic compounds degradation, and genes associated with HCN and siderophores synthesis; we also found a repertoire of genes associated with metal internalization and metabolism, sulfate/sulfonate and cysteine metabolism, oxidative stress and DNA repair. These findings reveal the genomic basis for the adaptation of this bacterium to the harsh environmental conditions from where it was isolated. Gene clusters associated with ectoine, terpene, resorcinol, and emulsan biosynthesis that can confer some competitive advantage were also found. Experimental results showed that Mc250 was able to reduce (∼60%) the virulence phenotype of the plant pathogen Xanthomonas citri subsp. citri when co-inoculated in Citrus sinensis, and was able to eradicate 98% of juveniles and stabilize the hatching rate of eggs to 4% in two species of agricultural nematodes. These results reveal biotechnological potential for the Mc250 strain and warrant its further investigation as a biocontrol and plant growth-promoting bacterium.